Drama works of Yaroslava Pulinovich (aspects of poetics) - Goncharova-Grabovskaya, Svetlana Y. (Journal of the Belarusian State University. Philology, 2020)
I describe the aspects of poetics in drama works by Yaroslava Pulinovich, a representative of the newest Russian drama. Analyzing her plays («I won’t come back», «Natasha’s dream», «My way», «I won», «How I became...», «Somnambulism», «Janna», «Elsa’s land», etc.). I itemize means and methods of drama structure elicitation (plenty of monologues of different kinds, such as confession monologue, memories monologue, inner monologue; narration from the first person, expanded remarks, epenthetic constructions, e. g. «little chapters», tales, etc.). The principle which organizes literary material (a story or an episode of character’s life, narration from the first person, expanded commentary remarks) is what predetermined architectonics of the plays: numbered «stories-chapters» instead of drama acts, fragmentation of episodes and scenes, montage of them. At the same time the epical doesn’t dominate the dramatical. I pay attention to the inner self-analytic conflict which allow give a deeper reveal of protagonist character, his or her psychology and perception, attitude to the surrounding people, critical view to the events. It is said about specifics of space and time continuum of the plays which is cinematographic in its essence (the locuses are: hostel, railway station, cafe, canteen, school, children’s home, etc.). The key topos of the spaces is «another’s home» or dysfunctional «own home». I come to conclusion about the novelty in the interpretation of character (self-affirming character) and show its distinction from the characters of «new drama» plays (self-identification, self-analysis, self-affirmation, belief in the best, etc.). Ya. Pulinovich dissects her characters’ psychology, worldview, dynamics of thought, formation, not just of age but also of soul. The playwright takes up an issue of a human (of different ages) in contemporary society, tries to find the cause (upbringing in a children’s home or incomplete family, relations between fathers and children) which influence the formation of contemporary people.